The co-constitution of the self and the world: action and proprioceptive coupling - Gapenne, Olivier (Frontiers in Psychology, 2014)
This article proposes a theoretical reflection on the conditions for the constitution of a distinction between the self and the world by a cognitive system. The main hypothesis is the following: proprioception, as a sensory system that is habitually dedicated essentially to experience of the body, is conceived here as a coupling which is necessary for the dual and concomitant constitution of a bodily self and of a distal perceptual field. After recalling the singular characteristics of proprioceptive coupling, three lines of thought are developed. The first, which is notably inspired by research on sensory substitution, aims at emphasizing the indispensable role of action in the context of such perceptual learning. In a second part, this hypothesis is put to the test of opposing arguments. In particular, we shall discuss, in the context of what Braitenberg called a synthetic psychology, the emergence of oriented behaviors in simple robots that can be regulated by sensory regulations which are strictly external, since these robots do not have any form of “proprioception”. In the same vein, this part also provides the opportunity to discuss the argument concerning a bijective relation between action and proprioception; it has been argued by others that because of this strict bijection it is not possible for proprioception to be the basis for the constitution of an exteriority. The third part, which is more prospective, suggests that it is important to take the measure of the phylogenetic history of this exteriority, starting from unicellular organisms. Taking into account the literature which attests the existence of proprioception even amongst the most elementary living organisms, this leads us to propose that the coupling of proprioception to action is very primitive, and that the role we propose for it in the co-constitution of an exteriority and self is probably already at work in the simplest living organisms.